EPCT-05. A PHASE 1/2 STUDY OF AVAPRITINIB FOR KIT- OR PDGFRA-MUTANT PEDIATRIC RELAPSED/REFRACTORY SOLID TUMORS. (1st June 2021) - Chi, Susan; Hsieh, Antony; Foley, Megan; Shi, Hongliang; Swamy, Preethi; Rodstrom, Jill; Rudoltz, Marc
Abstract: Prognosis for pediatric patients with advanced relapsed/refractory (R/R) solid (including central nervous system [CNS]) tumors is poor; targeted therapies achieve response rates of only 15%. Germ cell tumors and high-grade glioma (HGG) are the most common with KIT mutations; sarcoma and HGG are the most common tumors with platelet-derived growth factor receptor alpha ( PDGFRA ) mutations. Two-year overall survival is <10% for pediatric patients with diffuse intrinsic pontine glioma, often driven by PDGFRA mutations. No KIT/PDGFRA targeted therapies are currently approved for pediatric patients with R/R solid tumors. The selective KIT and PDGFRA inhibitor, avapritinib, demonstrated potent activity against KIT activation-loop (exon 17), juxtamembrane (exon 11), and extracellular-domain (exon 9) mutants (IC50 <2 nM), and PDGFRA activation-loop (D842V) mutants (IC50 =0.24 nM). CNS penetration in preclinical models (brain-to-plasma ratios at steady-state ranging from 0.74–1.00) demonstrated potential for activity against CNS tumors. Avapritinib is approved for the treatment of adults with unresectable/metastatic gastrointestinal stromal tumors (GIST) harboring PDGFRA exon 18 mutations (including D842V) in the USA based on an overall response rate ³84% with 59% response durations >6 months, and in the EU for adults with unresectable/metastatic GIST harboring a PDGFRA D842V mutation. The objectives of this 2-part phase 1/2 multicenter, open-label study, anticipated to enroll 31 patients from Q3 2021, are to assess avapritinib safety, preliminary efficacy, and pharmacokinetics in pediatric patients with KIT/PDGFRA-mutant solid R/R tumors. Eligible patients are aged 2 to <18 years with no alternative treatment options. Part 1 will enroll ≥6 patients; primary endpoint is confirmed age and body surface area physiologically-based pharmacokinetic modeling dose to provide equivalent exposure to the 300 mg adult avapritinib dose. Part 2 will enroll ≥25 patients at the recommended modeled avapritinib dose from Part 1; primary endpoint is overall response rate. Avapritinib once-daily will be administered in continuous 28-day cycles.